A boy with a recurrent intussusception within 48 hours – a vague hint not to be missed in primary care - Shalihin, Mohd Shaiful Ehsan; Mohd Din, Nina Syazmeen (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Intussusception is the most common paediatric abdominal emergency in young children. Even though red current jelly stool is the pathognomonic feature, it only presents in less than 15% of cases. The clinical diagnosis is often missed as the presentation can mimics others. A recurrent case within 48 hours of reduction is even rare and can be falsely suspected as a normal post-reductive presentation. We highlighted a recurrence of intussusception in a 3-year-old boy, who was initially well after being discharged to home. Medical attention was sought initially but was informed that the clinical presentation could be resolved in a few days. Nevertheless, a second opinion has been sought in view of the persistent frequency pattern. Without delay, readmission of the child was arranged for surgical reduction. Regardless of the mild severity of gastrointestinal symptoms, the possibility of recurrence of intussusception should be suspected despite the presumed success of the initial intervention. Malaysian Journal of Medicine and Health Sciences (2024) 20(5): 424-426. doi:10.47836/mjmhs20.5.50